A low-temperature prepared composite coating to protect SiC-coated C/C composites against oxidation in a wide temperature range for long-life service. Issue 10 (August 2023) - Zhu, Xiaofei; Zhang, Yulei; Zhang, Jian; Li, Tao; Jung, In-Ho; Su, Yangyang; Gai, Wenhan
Abstract: To improve the oxidation resistance of carbon/carbon (C/C) composites in a wide temperature range (1173–1773 K), a composite coating containing rich B2 O3 glass was prepared on SiC-coated C/C composites by slurry dipping-densifying at low temperature. Borosilicate and SiO2 glasses acted as oxygen barriers at low and medium-high temperatures, respectively. Besides, Hf-oxides (HfO2, HfSiO4 ) ceramic particles improved the thermal stability of the glass and enhanced the crack resistance of glass layer. Therefore, the composite coating can effectively protect C/C composites against oxidation for 403 h at 1173 K, 723 h at 1473 K and 403 h at 1773 K with the mass gain of 3.77 g·m −2, 21.41 g·m −2 and 0.42 g·m −2, respectively. After 50 times thermal cycles between room temperature and 1773 K, the mass gain of the coated sample was 3.95 g·m −2 and the mass retention rate was up to 98.19 % during the thermos-gravimetric test from room temperature to 1773 K.